2006
DOI: 10.1155/2006/395391
|View full text |Cite
|
Sign up to set email alerts
|

Polyaniline Conducting Electroactive Polymers Thermal and Environmental Stability Studies

Abstract: Abstract:In the current studies, polyaniline (PANi) was prepared both chemical and electrochemically in the presence of different bronsted acids from aqueous solutions. The effect of thermal treatment on electrical conductivity, and thermal stability of the PANi conducting polymers were investigated using 4-point probe and TGA techniques respectively. It was found that polymer prepared by CV method is more thermally stable than those prepared by the other electrochemical techniques. In this paper we have also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
74
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(85 citation statements)
references
References 41 publications
10
74
0
1
Order By: Relevance
“…The smooth thermogram shows only one exothermic peak at 668 K, where thermal decomposition of polyaniline takes place. Ansari and Keivani (2006) obtained the similar behavior of polyaniline prepared by cyclic voltammetry and reported that the polyaniline prepared by cyclic voltammetry is highly thermal stable than that of prepared by potentiostatic mode.…”
Section: Thermo-emf Measurementmentioning
confidence: 70%
“…The smooth thermogram shows only one exothermic peak at 668 K, where thermal decomposition of polyaniline takes place. Ansari and Keivani (2006) obtained the similar behavior of polyaniline prepared by cyclic voltammetry and reported that the polyaniline prepared by cyclic voltammetry is highly thermal stable than that of prepared by potentiostatic mode.…”
Section: Thermo-emf Measurementmentioning
confidence: 70%
“…Similar to metals, it owns unusual electronic, magnetic, electrochemical and optical properties jointly with high environmental stability, easy polymerization and low cost of monomer. However, its processability by melting is not practical since the polymer decomposes at temperatures below its softening or melting point [1][2][3][4] . Basically, in the previous published articles, the presence, absence and type of dopant agent besides the thermal treatment on its behavior have been highlighted.…”
Section: Introductionmentioning
confidence: 99%
“…These protonated polymers were stable up to 200 ∘ C. Chen [18] compared the thermal stability of emeraldine base and emeraldine salt. The highest thermal degradation temperature of emeraldine salt was found to be 410 ∘ C while for emeraldine base it was 450 ∘ C. Ansari and Keivani [19] synthesized emeraldine salt in the presence of different bronsted acids such as hydrochloric acid (HCl), sulfuric acid (H 2 SO 4 ), and 8-hydroxypyrene-1,3,6-trisulfonate (HPTS). They found that thermal stability of the synthesized emeraldine salt was highly dependent on the nature and size of the dopant used.…”
Section: Journal Of Chemistrymentioning
confidence: 99%
“…All the above studies reveal that the method of synthesis is important in determining the thermal stability of the polymer. Generally a three-step decomposition process has been observed for the emeraldine salt [9,19]. In this process the initial stage of weight loss is due to the volatilization of water molecules; then at higher temperatures the protonic acid component of the polymer is lost and finally at more extreme temperatures the degradation of the polymer can lead to production of gases such as acetylene and ammonia or amorphous carbon [19,24].…”
Section: Journal Of Chemistrymentioning
confidence: 99%